Influence of exogenous enzymes and pelleting on feed manufacturing and broiler performance - Truelock, Courtney Nicole (Kansas State University, 2020)
A multitude of exogenous enzymes, such as phytase, amylase, and protease, have been developed to improve nutrient digestion in monogastrics. The majority of monogastric feed is pelleted, and the efficacy of these enzymes in pelleted diets requires some investigation. Heat, moisture, and mechanical pressure associated with pelleting are known to alter enzyme structure and activity. Thus, it is probable any one of the pelleting variables could inactivate exogenous feed enzymes and reduce their feeding value. The objectives of this dissertation were to determine the effects of pelleting parameters and phytase sources on phytase stability during pelleting, evaluate the influence of corn type on starch gelatinization of pelleted diets and subsequent broiler performance, and examine the efficacy of protease in poultry diets. The first set of experiments evaluated the effect of phytase source, conditioning temperature, conditioner retention time, steam pressure, and die thickness on phytase stability and pellet quality. These results indicated a negative linear relationship between conditioning temperature and phytase stability that is influenced by phytase source. Additionally, increasing conditioning temperature increases pellet durability and hot pellet temperature. Even at the lowest conditioning temperature of 74°C, maximum phytase stability averaged 63% in pellets. There was no evidence that conditioner retention time or die L:D affected phytase stability, and increasing steam pressure tended to improve phytase recovery by 18% in pellets. The second experiment determined the effects of die thickness and conditioning temperature on pelleting and starch characteristics in diets containing conventional or Enogen® Feed corn, a high amylase corn variety. It was concluded that starch gelatinization increased with increasing conditioning temperature, and Enogen® Feed corn diets resulted in greater starch gelatinization than conventional corn diets. Furthermore, die thickness had no effect on starch characteristics, improved pellet durability, and increased pellet mill energy consumption. The third experiment evaluated the effects of corn type and conditioner retention time on pelleting characteristics of a poultry diet and subsequent broiler growth performance and carcass traits. The results demonstrated broilers fed Enogen® Feed corn consumed more feed, had heavier body weights, and heavier carcasses than broilers fed conventional corn, however there was no difference in carcass feed efficiency between treatments. Moreover, pelleting of Enogen® Feed corn resulted in greater starch solubility in cooled pellets compared to pelleted conventional corn diets, and broiler performance was not affected by conditioner retention time. Lastly, the fourth experiment examined the effects of dietary Lys concentration and exogenous protease inclusion on growth performance and amino acid digestibility in poultry. It was concluded that broilers fed 1.12 and 1.21% digestible Lys diets with added protease had a 2-point improvement in FCR compared to chicks fed these diets without protease. Increasing digestible Lys concentration improved FCR in broilers and poults and improved BW, ADG, and ADFI in poults. There was no evidence that added protease had an effect on BW, ADG, or ADFI in broilers or poults. Finally, ileal amino acid digestibility was not affected by digestible Lys or protease inclusion for either 20-d old broiler chicks or 42-d old turkey poults.
Keywords: Exogenous enzymes; Pelleting; Broiler performance